(untitled) (Universal International Scientific Journal, 2026)
: in the context of neurodigital civilization, the role and importance of national education are analyzed in an era of increasing information flow, digital technologies and global ideological influences on the minds of young people. The main goal of the study is to identify effective mechanisms for the formation of cognitive-ideological resistance in young people based on national values, traditions and spiritual heritage.